Sink feedback regulation of photosynthesis in vines: measurements and a model - Quereix, Anne; Dewar, Roderick C.; Gaudillere, Jean‐Pierre; Dayau, Sylvia; Valancogne, Charles (Journal of experimental botany, 2001)
An experimental and modelling study of source–sink interactions in Vitis vinifera L., cv. Cabernet Sauvignon, rooted cuttings under non‐limiting environmental conditions with a 12 h photoperiod is presented here. After 4 h, measured photosynthesis, stomatal conductance and leaf carbohydrate content reached maximum values. Over the remainder of the photoperiod, photosynthesis and stomatal conductance decreased continuously, whereas leaf carbohydrate content remained relatively constant. Because the experiment took place in a non‐limiting environment, the results suggest that stomatal regulation of photosynthesis was mediated by an internal factor, possibly related to sink activity. A simple 1‐source, 2‐sink model was developed to examine the extent to which the data could be explained by a hypothetical sink‐to‐source feedback mechanism mediated by carbohydrate levels in either the mesophyll, the source phloem or the phloem of one of the two sinks. Model simulations reproduced the data well under the hypothesis of a phloem‐based feedback signal, although the data were insufficient to elucidate the detailed nature of such a signal. In a sensitivity analysis, the steady‐state response of photosynthesis to sink activity was explored and predictions made for the partitioning of photosynthate between the two sinks. The analysis highlights the effectiveness of a phloem‐based feedback signal in regulating the balance between source and sink activities. However, other mechanisms for the observed decline in photosynthesis, such as photoinhibition, endogenous circadian rhythms or hydraulic signals in the leaf cannot be excluded. Nevertheless, it is concluded that the phloem‐based feedback model developed here may provide a useful working hypothesis for incorporation into plant growth models and for further development and testing.